Penggunaan Jaringan Sistem IPTV (Internet Protocol Television) User-Client dengan Pemanfaatan Fasilitas BOX TV, Android dan Windows - Gunawan, Indra; Sumarno, Sumarno; Tambunan, Heru Satria (Building of Informatics, Technology and Science (BITS), 2019)
IPTV (Internet Protocol Television) networks are some of the types of terrestrial networks using internet facilities through a packet provided through a packet switched network infrastructure such as broadband access. The use of the IPTV system can be done through account facilities provided and provided to users, where the facilities of the accounts obtained are terrestrial facilities that can pamper users by watching premium facilities or programs that can be enjoyed. With the development of the use of the internet and bandwidth speeds that can be obtained or used by users, the use of the IPTV network system can be used optimally. The use of the IPTV system through the account provided can be utilized by using the facilities found in some TV BOX and Android. Besides being able to be used at home if using BOX TV, Android and Windows, this IPTV system can also be used outside the home with facilities provided by devices embedded with the Android and Windows operating systems. So, all types of information needed by users must be quickly and responsibly accepted immediately, so there is no limited information needed.